Bangladesh : Agricultural Insurance Solutions Appraisal Technical Report - World Bank Group (World Bank, Washington, DC, 2018)
Agriculture is a key sector in Bangladesh, but it is highly exposed to risks. While agriculture is a source of employment and livelihood for nearly one in two adults in Bangladesh and contributes about 16 percent to GDP, it is highly exposed to natural hazards. Indeed, Bangladesh is commonly ranked as one of the most vulnerable countries in the world to natural disasters with agriculture heavily exposed to floods, cyclones, and drought. In 2007, for instance, Cyclone Sidr destroyed 0.69 million ha of cultivated crop lands and killed over 460,000 head of livestock and poultry.In the past, the government of Bangladesh and development partners have provided substantialsupport to farmers in the aftermath of large disasters, but this approach has disadvantages in that support is not guaranteed to farmers and may be slow. In the aftermath of Cyclone Sidr,recovery and reconstruction needs were estimated at USD 1.3 billion, or 28 percent of governmentexpenditures. In spite of efforts by the government of Bangladesh, the gap between available funding and needs is often large and can reach more than USD 1.5 billion in bad years (Air Worldwide and ADPC 2014). Bangladesh often relies on international assistance, as over the past ten years, only 33 percent of disaster-related expenses has been met by domestic resources. In addition, disaster relief transfers often take substantial time to reach beneficiaries and require to divert resources away from long term development projects. Agricultural insurance offers the government a planned, fast, ex ante alternative to ad hoc disaster response, one that (1) reduces the ex post fiscal burden on the government, (2) improves farmers’ resilience to shocks, and (3) supports the expansion of agricultural credit. Every five years on average in Bangladesh, production shocks lead to a drop of up to 50 percent in crop income available for consumption in average rural households. This drop pushes many small- and medium- scale farmers into poverty. Although many Bangladeshi farmers can access credit, their exposure to risks makes formal financial institutions reluctant to lend to them, so that most farmers borrow from informal lenders at average annual interest rates ranging from 19 percent to 30 percent. Agricultural insurance transfers risk away from farmers, and therefore benefits financial institutions and the government of Bangladesh as well as the farmers themselves.